LECTIN-DEPENDENT DIVERSITY OF NATURAL KILLER POPULATIONS AND COMMUNICATIONS AGAINST TUMORS AND VIRUSES - M. V. Lakhtin (SPb RAACI, 2019)
Response of human natural killer (NK) cell populations (NKP) against tumors in the presence of viruses was evaluated as a quite variable, early adapting for the pathological signals in organism, mobile and selective combination agents. NKP act as a result of co-functioning between the receptor lectins (RL) recognizing glycopatterns (RL as triggers, initiators and basic agents for coupled activities), and Ig-like, cytotoxic and other additional  communicative and effector receptors (superstructural, tuning for achievement of final effector-type NKP constructions required), and their ligands (modulators of final cell surface receptor mosaics). Such NKP created play important role in redistribution of NKP-induced antitumor/ antiviral cytokines in organism. Intercellular communicative potential of NKP also involves other innate and innate-like cells. Such extended communications of NKP provide a prospective and universal resource of human protection. NKP must be under consideration upon development of new maneuvre and relilable prophylactic and immunotherapeutic antitumor/ antiviral systems and vaccine strategies. The ways for the fine tuning (RL—KIR/ NCR/ CD/ their combinations) algorithms of RL-based creation of antitumor/ antiviral NKP are revealed. Key role is given to screening spectrum of patient NKP for development of communicative anticancer/ antiviral strategies. The status of NK compartment will characterize resistance of individuum/ contingent of individuums to viral infections of epidemiological significance, will play important role in anti-epidemic protection of regional population.